Polyelectrolyte Complexes: Phase Diagram and Intrinsic Viscosities of the System Water/Poly(2-vinylpyridinium-Br)/Poly(styrene sulfonate-Na) - Bercea, Maria; Nita, Loredana-Elena; Eckelt, John; Wolf, Bernhard A. (Macromolecular chemistry and physics, 2012)
In contrast to all earlier work on that subject, measurements are performed at high dilution up to total polymer concentrations wpol of 0.5 wt%. Aqueous solutions of poly(2‐vinylpyridinium‐Br) and of poly(styrene sulfonate‐Na) are only fully miscible if wpol < 0.02 wt%. Decomposition into two liquid phases is observed upon an increase in wpol, where the extension of the miscibility gap is considerably larger at 60 than at 25 °C. Viscosity measurements demonstrate that the formation of the polyelectrolyte complexes may take hours. The intrinsic viscosity of the polyanion turns out to be 20 times larger than that of the polycation and to be much more sensitive toward the addition of extra salt. The [η] values of the blend pass a minimum as a function of its composition. It is demonstrated that the formation of polyelectrolyte complexes on a colloidal level—typical for sufficiently concentrated solutions—is at low polymer concentration and in the absence of extra salt preceded by liquid/liquid phase separation. Viscosity measurements disclose that the formation of soluble polyelectrolyte complexes may take up to hours. The intrinsic viscosities of the blend pass a minimum as a function of its composition.